Iron and niobium based additives in magnesium hydride: Microstructure and hydrogen storage properties. (9th March 2017) - Floriano, R.; Deledda, S.; Hauback, B.C.; Leiva, D.R.; Botta, W.J.
Abstract: In this study, powder mixtures of MgH2 + 2 mol.% X, with X = Nb, Nb2 O5, NbF5, Fe, Fe2 O3, FeF3, were processed by mechanical milling at liquid nitrogen temperature (cryomilling). The effect of additives on crystalline structure, thermal properties and hydrogen storage properties of the mixtures were investigated. Morphological investigations indicated a heterogeneous particle size distribution of the powder mixtures and a fine dispersion of additive particles (FeF3 ) in the MgH2 matrix. High resolution synchrotron radiation X-ray diffraction (SR-XRD) data followed by Rietveld refinements showed a significant reduction on crystallite size for the samples containing fluorides (11 nm) in comparison with the pure MgH2 sample (29 nm). This was related to the mechanical behavior of fluorides during milling with MgH2, which act as a lubricant, dispersing and/or cracking agent during milling, and thus helping to further reduce MgH2 particle size. DSC analysis revealed that fluorides (NbF5, FeF3 ) are much more effective than oxides (Nb2 O5, Fe2 O3 ) and the transition metals (Nb and Fe), respectively, in reduction the desorption temperature. Furthermore, Nb2 O5 is more efficient than Fe2 O3 . Finally, the best results for desorption kinetics were observed for the fluorides: NbF5 and FeF3 (equivalent effect and consistent to the DSC analysis) followed by the oxides: Nb2 O5, Fe2 O3 and Nb. The addition of Fe was not efficient in comparison with the pure cryomilled sample. Highlights: The positive effects of iron and niobium based additives were investigated during milling at low temperature. There is a strong mechanical effect when fluorides are milled together with MgH2 resulting in a much finer microstructure. Low desorption temperatures and enhanced kinetics behavior of MgH2 -samples are reported.